2011
DOI: 10.4238/2011.october.13.1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of complex vertebral malformation carriers in Holstein cattle in south China

Abstract: ABSTRACT. Complex vertebral malformation (CVM) is a recently described monogenic autosomal recessive hereditary defect of Holstein dairy cattle that causes premature birth, aborted fetuses and stillborn calves. Guanine is substituted by thymine (G>T) in the solute carrier family 35 member A3 gene (SLC35A3). A valine is changed to a phenylalanine at position 180 of uridine 5'-diphosphate-N-acetylglucosamine transporter protein. CVM is expected to occur in many countries due to the widespread use of sire semen. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…A missense mutation in SLC35A3 gene has been associated with complex vertebral malformations in bovine and revealed a new mechanism for malformation of the vertebral column caused by abnormal nucleotide sugar transport into the Golgi apparatus ( Thomsen et al., 2006 ). Some other studies have also identified SLC35A3 as having an important role in vertebral malformations ( Ghebranious et al., 2006 , Ruść and Kamiński, 2007 , Chu et al., 2008 , Ghanem et al., 2008 , Ghanem et al., 2009 , Wang et al., 2011 ).
Figure 5 Results of haplotype-based genome-wide association studies using PLINK for metatarsus circumference (MeC).
…”
Section: Resultsmentioning
confidence: 93%
“…A missense mutation in SLC35A3 gene has been associated with complex vertebral malformations in bovine and revealed a new mechanism for malformation of the vertebral column caused by abnormal nucleotide sugar transport into the Golgi apparatus ( Thomsen et al., 2006 ). Some other studies have also identified SLC35A3 as having an important role in vertebral malformations ( Ghebranious et al., 2006 , Ruść and Kamiński, 2007 , Chu et al., 2008 , Ghanem et al., 2008 , Ghanem et al., 2009 , Wang et al., 2011 ).
Figure 5 Results of haplotype-based genome-wide association studies using PLINK for metatarsus circumference (MeC).
…”
Section: Resultsmentioning
confidence: 93%
“…Rezaee et al (2009) screened 144 Iranian Holsteins but found no carriers among the lot while, Alaie et al (2012) screened 100 Holsteins and 100 Guilan cows by PCR-SSCP method but found no carriers among Iranian cattle. Wang et al (2011) detected 10 CVM carriers out of 342 studied animals (2.9% carrier frequency). In another study, Zhang et al (2012) used real-time PCR assay and detected 56 out of 587 animals studied in Chinese cattle, with 1.36% heterozygous carrier frequency.…”
Section: Discussionmentioning
confidence: 96%
“…Amplification of CRS-PCR was performed with F: 5′-GC TCTCCTCTGTAATCCCCA-3′ and R: 5′-CCACTGGAAA AACTAGCTGTGAGTA-3′ primer pairs [ 25 ] under the following conditions: denaturing at 95℃ for 2 min and 35 cycles of 95℃ for 30 sec, 60℃ for 30 sec, 72℃C for 30 sec, and final extension at 72℃ for 10 min. Amplicons were restricted by using the Rsa I fast digest enzyme (Thermo Scientific, USA) at 37℃ for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, studies to identify CVM carriers were conducted in Japan [ 11 16 ], Germany [ 14 ], Sweden [ 5 ], Czech Republic [ 8 ], Poland [ 20 ], Turkey [ 15 ], China [ 7 23 26 27 ], Slovakia [ 10 ], and Iran [ 12 19 ]. Allele-specific polymerase chain reaction (AS-PCR) [ 11 ], created restriction-site PCR (CRS-PCR) [ 25 ], PCR with primer-introduced restriction analysis (PCR-PIRA) [ 13 ], and DNA sequencing [ 15 ] methods have been reported as capable of detecting the mutant allele that causes the CVM disorder. The aim of this study was to compare the sensitivity, specificity, positive and negative predictive values, accuracy, and rapidity of the AS-PCR, PCR-PIRA, and CRS-PCR methods and to determine the most accurate one for screening the mutant allele in SLC35A3 gene in a Holstein cattle population.…”
Section: Introductionmentioning
confidence: 99%